Sustainable Digital Marketing and Service Quality as Drivers of Customer Loyalty: : The Mediating Role of Trust in MSMEs - Flowry Charles Pangkey; Lilly Linne Kainde (Economics and Digital Business Review, 2026)
This study examines the influence of Sustainable Digital Marketing (SDM) and Service Quality on customer trust and loyalty in Micro, Small, and Medium Enterprises (MSMEs), with a focus on youth-based community markets in North Sulawesi. Using a descriptive correlational design and data collected from 325 respondents, the analysis was conducted through Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both direct and indirect relationships. The results show that SDM has a significant direct effect on customer loyalty but does not influence trust, suggesting that sustainability-oriented digital communication strengthens loyalty through value alignment rather than relational confidence. Service Quality is found to strongly enhance trust but does not directly affect loyalty, indicating that trust functions as a key psychological bridge in forming long-term customer commitment. Mediation analysis confirms that trust significantly mediates the relationship between Service Quality and Customer Loyalty, while the relationship between SDM and loyalty is not mediated by trust. Summary of results the study extends the Commitment on Trust Theory within the MSME context and highlights that customer loyalty can emerge through two routes: directly through sustainable digital practices and indirectly through trust formed by consistent service delivery. These findings emphasize the importance of integrating ethical digital communication with reliable and empathetic service performance to strengthen long-term loyalty among young consumers.